Sesquiterpenes and Cyclodepsipeptides from Marine-Derived Fungus Trichoderma longibrachiatum and Their Antagonistic Activities against Soil-Borne Pathogens - Du, Feng-Yu (Mar Drugs, 2020)
Soil-borne pathogens, including phytopathogenic fungi and root-knot nematodes, could synergistically invade vegetable roots and result in serious economic losses. The genus of Trichoderma has been proven to be a promising reservoir of biocontrol agents in agriculture. In this study, the search for antagonistic metabolites from a marine-derived fungus, Trichoderma longibrachiatum, obtained two structural series of sesquiterpenes 1–6 and cyclodepsipeptides 7–9. Notably, the novel 1 was a rare norsesquiterpene characterized by an unprecedented tricyclic-6/5/5-[4.3.1.0(1,6)]-decane skeleton. Their structures were elucidated by extensive spectroscopic analyses, while the absolute configuration of novel 1 was determined by the comparison of experimental and calculated ECD spectra. The novel 1 and known 2 and 3 showed significant antifungal activities against Colletotrichum lagrnarium with MIC values of 8, 16, and 16 μg/mL respectively, even better than those of the commonly used synthetic fungicide carbendazim with 32 μg/mL. They also exhibited antifungal potential against carbendazim-resistant Botrytis cinerea. Cyclodepsipeptides 7–9 showed moderate nematicidal activities against the southern root-knot nematode (Meloidogyne incognita). This study constitutes the first report on the antagonistic effects of metabolites from T. Longibrachiatum against soil-borne pathogens, also highlighting the integrated antagonistic potential of marine-derived T. Longibrachiatum as a biocontrol agent.